2013
DOI: 10.1111/j.2041-1626.2012.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dental health status and dental health behavior among Sana'a University students, Yemen

Abstract: The dental health and toothbrushing behaviors of Sana'a University students are unsatisfactory, and influenced unequally by different factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 29 publications
4
21
1
Order By: Relevance
“…Self-neglect was considered the least important reason for personal oral health negligence. These findings are similar to the previous studies conducted by Al Kawas et al 28 , Al-Hussaini et al 29 and Halboub ES et al 30 Although the current study provides some information on the oral health behaviour among the dental professionals in this group, there is a need for further detailed studies among dental professionals to address this important subject. The factors affecting the oral health care such as fear of cross infection and the awareness of oral health care need to be evaluated and addressed further.…”
Section: Discussionsupporting
confidence: 92%
“…Self-neglect was considered the least important reason for personal oral health negligence. These findings are similar to the previous studies conducted by Al Kawas et al 28 , Al-Hussaini et al 29 and Halboub ES et al 30 Although the current study provides some information on the oral health behaviour among the dental professionals in this group, there is a need for further detailed studies among dental professionals to address this important subject. The factors affecting the oral health care such as fear of cross infection and the awareness of oral health care need to be evaluated and addressed further.…”
Section: Discussionsupporting
confidence: 92%
“…Healthy habits and good oral hygiene, including twice daily tooth brushing, are critical in preventing gum disease and maintaining good oral health [ 1 ]. The prevalence of less than twice tooth brushing per day among university students seems to be higher in low and middle income than in high income countries, e.g., 52.2% in India [ 2 ], 35% in Lebanon [ 3 ], 32% in Turkey [ 4 ]; 24% not regularly in Yemen [ 5 ]) than in high income countries (7.9% in Italy [ 6 ], 25% in USA [ 7 ]). Similarly, the prevalence of less than an annual dental check-up among university students also seem to be higher in developing countries (84% in Kenya [ 8 ], 92.2% in Nigeria [ 9 ], 70% in Turkey [ 4 ]; 42.7% in India never had a dental visit [ 2 ] and 48.2% in Iran never visited the dentist [ 10 ]) than in industrial countries (41% in Finland [ 11 ] and 40.1% in Italy [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors have been found to be associated with suboptimal tooth brushing among young people, including sociodemographics such as men [ 3 , 7 , 12 , 13 , 14 , 15 , 16 ] and lower socioeconomic status [ 17 , 18 , 19 ]; poor oral health attitude [ 2 ]; addictive risk behaviour such as smoking [ 5 , 13 ] and alcohol and cannabisuse [ 20 ]; lack of exercises [ 3 ], dietary behaviour, including infrequent fruits and/or vegetables consumption [ 21 , 22 , 23 ], frequent servings of chocolate, candy or chips/day [ 3 ], and poor mental health or psychological distress [ 21 ]. Less than annual or no dental visits has been found to be associated with being male [ 15 , 24 , 25 , 26 , 27 ], lower socioeconomic status [ 16 , 26 , 28 ], younger age [ 9 ]; poor oral health attitudes [ 25 ]; health risk behaviour, including infrequent tooth brushing [ 26 ], smoking [ 29 ] and anticipation of painful treatment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the study by Babaei indicated that 59.5% of students brush their teeth daily [21]. In the study by Halboub, the frequency of tooth brushing (less than twice per day) was reported as 24% [22]. Considering the discrepancy of the age group across different studies, the different findings seem to be normal.…”
Section: Discussionmentioning
confidence: 98%